1998
DOI: 10.1093/carcin/19.1.117
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the tumors induced by coal tar and benzo[a]pyrene in a 2-year bioassay

Abstract: The tumorigenicity of two coal tar mixtures was compared to that of benzo[a]pyrene after 2 years of feeding. Mixture 1, a composite of coal tar from seven coal gasification plant waste sites, was fed to female B6C3F1 mice (48 mice per group) for 2 years at doses of 0.0, 0.01, 0.03, 0.1, 0.3, 0.6 and 1.0%. Mixture 2, which was composed of coal tar from two of the seven waste sites and another site having a high benzo[a]pyrene content, was fed at doses of 0.0, 0.03, 0.1 and 0.3%. Additional groups of mice were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
243
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(256 citation statements)
references
References 17 publications
8
243
2
3
Order By: Relevance
“…40 Epidemiologic studies have directly investigated the association between dietary intake of PAHs and colorectal neoplasms and found a positive association between benzo(a)-pyrene and CRA. 41 The high saturated fat content of red and processed meat is also the proposed culprit for the increased …”
Section: Discussionmentioning
confidence: 99%
“…40 Epidemiologic studies have directly investigated the association between dietary intake of PAHs and colorectal neoplasms and found a positive association between benzo(a)-pyrene and CRA. 41 The high saturated fat content of red and processed meat is also the proposed culprit for the increased …”
Section: Discussionmentioning
confidence: 99%
“…Lung tumors were not observed when BaP was administered in the diet to B6C3F1 mice (Culp et al, 1998). In studies of lung tumor induction by implantation in rats, BaP is more carcinogenic than the benzofluoranthenes or indeno [1,2,3-cd]pyrene (Deutsch-Wenzel et al, 1983).…”
Section: Tobacco Smoke Carcinogens and Cancermentioning
confidence: 99%
“…N-nitrosodiethylamine and N-nitrosopiperidine are two other smoke constituents that could be involved in esophageal tumor induction in smokers. BaP induces some esophageal tumors when administered to mice in the diet (Culp et al, 1998). The risk for esophageal cancer in humans is also enhanced by alcohol consumption (McCoy and Wynder, 1979).…”
Section: Tobacco Smoke Carcinogens and Cancermentioning
confidence: 99%
“…Parallel treatment with B[a]P induced tumors of the forestomach, esophagus, and tongue. A comparison of the results indicated that the lung and liver tumors appeared to be due to other genotoxic components in coal tar besides B[a]P (Culp et al 1998). Many PAHs have been tested by topical application to the skin of mice or by subcutaneous injection to identify the relationship between structural characteristics of the compounds, their metabolism, and tumorigenic potency.…”
Section: Pahs and Human Carcinogenesismentioning
confidence: 99%